The Effect of Moderating Noise Pollution on Premature Infants' Behavioral and Physiological Responses in Neonatal Intensive Care Unit - Khajeh 1, Mahboobeh; Bahramnezhad 2*, Fatemeh; Dehghanzadeh 3, Shadi; Fadaee Aghdam 1, Nasrin; Bagheri 1, Hossein; Baha 4, Robabe (Shahroud Journal of Medical Sciences, 2020)
Background: The aim of the study was to determine the effect of moderating noise pollution on premature infants' behavioral and physiological responses in a neonatal intensive care unit (NICU).Methods: 110 premature infants hospitalized in the NICU ward of hospitals in Tehran were selected. All the infants who met the research criteria were allocated and assigned to the experimental and control group (n = 55). The sampling method was non-probability and convenient. In the first section of time, each infant with inclusion criteria, inserted in the control group and then in the second section of time, infant with inclusion criteria placed in the experiment group. In the first section, the educated nurse measured the LAeq, LC, LA, infants’ behavioral responses, and physiological responses. In the second section, noise modifying interventions were implemented in the experimental group for 6 weeks, and then LAeq, LC, LA, infants’ behavioral responses and physiological responses were measured with the same methods.Results: Infants' heart rate in the experimental group was significantly lower than the control group (Pvalue<0.05), and atrial blood O2 Saturation was significantly higher than the control group (Pvalue<0.05). There was no statistically significant difference in the mean number of crying, sleeping, and Moro reflex of premature infants in the two groups. Also, the sound-pressure level in the C-weighted network in the experimental group was lower than the control group (Pvalue=0.021). The sound-pressure level of the C-weighted network was obtained in the same way (Pvalue=0.008).Conclusions: Based on the results, moderating noise pollution in NICU can lead to heart rate deceleration and atrial blood O2 Saturation acceleration in premature infants.Keywords: Noise pollution, Premature infants, Behavioral responses, Physiological responses, Neonatal Intensive care unit.